IN VARIOUS LAYER THICKNESSES EFFECT OF APPLICATION OF BAYSTAR DEFOLIANT ON THE YIELD OF COTTON VARIETY S-7303 - Mamatkulov Orifjon; Allanazarov Sultanbek (Innovate Conferences, 2025)
This study examined the effectiveness of the Baystar defoliant and its impact on the yield of the medium-fiber cotton variety S-7303 under different plant densities. The experiments were conducted at planting densities of 70–80 thousand plants/ha, 100–110 thousand plants/ha, and 130–140 thousand plants/ha. At each density level, low, medium, and high rates of defoliant were applied, and leaf drop dynamics, boll opening degree, and final yield indicators were analyzed. The results demonstrated that the optimal combination of plant density and defoliant rate is a crucial factor in improving both the quantity and quality of yield. These findings are of practical importance for improving cotton cultivation techniques, particularly for medium-fiber varieties, in order to achieve higher yields, efficiently manage the defoliation process, and enhance productivity.
Keywords: distribution, layer, early-maturing , late-maturing , plant density , thousand plants/ha , standard, background, q/ha, defoliant, rate, first harvest, second harvest, baystar , entodefol , control.